Multi-Scenario Simulation Evaluation and Strategic Zoning of Habitat Services Based on Habitat Quality and Ecological Network: A Case Study of Lanzhou City - Jin Shi; Xianglong Tang (ISPRS International Journal of Geo-Information)
Land management strategies play a pivotal role in the sustainable development of a region. Integrating space syntax into the ecological–social perspective to assess habitat services and optimize multi-scenario simulations and evaluations is crucial for developing resilient strategies for the future. This study takes Lanzhou, a semi-arid region, as a case study, combining multi-model analysis to explore the relationship between habitat quality and spatial accessibility and to conduct habitat service zoning. The findings indicate that under four development scenarios, the ecological network generally shows a three-segment distribution. The factors that have the most significant impacts on cultivated land, forests, shrubs, construction land, and bare land are GDP, precipitation, temperature, population density, and NDVI, respectively. The ecological priority scenario features the most corridors, while the cultivated land protection scenario incurs the lowest construction costs. Across various analysis radii of space syntax, except for MED at a 6000 m radius, the ecological priority scenario exhibits excellent network accessibility. The coupling coordination degree of the four scenarios generally lies within a mild imbalance level, with a spatial distribution pattern characterized by “high in the west and low in the east”. Based on 10 types of habitat services, a priority management sequence for land and key governance towns was established, leading to the proposal of a “dual coordination” multi-center compact network layout model. This research not only enriches the theory of land ecology but also overcomes the shortcomings in land spatial planning, addresses the practical problems of land development transformation in Lanzhou, and offers new data support and ideas for the construction of ecological cities in semi-arid regions.